Context is crucial: wading through public health information. (2nd September 2019) - Dockrell, Martin; Green, David
Abstract : Martin Dockrell andDavid Green explain how vital it is for health professionals to keep abreast of the latest information and advice on public health issues. In particular, advice on smoking cessation and the use of e-cigarettes is particularly relevant today